Uji Coba Bioinsektisida Terhadap Larva Anopheles spp. di Habitat Sungai Pada Musim Kemarau - Yamtana Yamtana; Damar Tri Boewono; Soeyoko Soeyoko (Poltekkes Kemenkes Yogyakarta, 2008)
The objective of the study was to determine the differences of the killing power effect amongst three type of bioinsecticides on Anopheles spp larvae living at puddles on river habitation during dry season. The type of the study was quasi experimental, and the treatment was aimed at puddles which act as breeding places for Anopheles spp on three river habitation in Kokap Sub-District, Kulon Progo Regency, Yogyakarta Province. The treatment were conducted by dripping a dose of 1 liter/ha liquid formulation of B. thuringiensis H-14 bioinsecticides to each of 15 puddles at Progo River; spreading a dose of 500 mg/ha granule formulation of B. thuringiensis bioinsecticides H-14 to each of 15 puddles at Tegiri River; and spreading a dose of 500 mg/ha granule formulation of B. sphaericus H-5a5b to each of 15 puddles at Geseng River. The control groups for each treatment were five puddles at the same river and were treated by blank formulation. Data was analyzed using Anova test version 10.0 for windows, and was followed by comparing only those in the treatment group using Duncan test. Liquid formulation of B. thuringiensis H-14, granule formulation of B. thuringiensis H-14, and granule formulation of B. sphaericus H-5a5b affected the decrease of Anopheles spp larvae density for more than 70% for 7 days, 7 days, and 14 days respectively. As Anova test showed a very significant differences (p<0.01), it can be concluded that there were significant differences of the killing power effect amongst the three type of bioinsecticides on the density of Anopheles spp larvae living at puddles on river habitation during dry season.